Experimental and Computational Analysis of Surgical Mask Effectiveness Against COVID-19 in Indoor Environment - Chin Yan Suen; Helen Hoi Ling Kwok; Yuk Hang Tsui; Ka Hei Lui; Hong Hang Leung; Ka Wo Lam; Karen Pik Shuen Hung; Joseph Kai Cho Kwan; Kin Fai Ho (Aerosol and Air Quality Research)
Abstract An experiment coupled with a computational analysis was conducted to investigate the effectiveness of surgical masks, which include KF94 and ASTM Level 1, in an indoor environment. The KF94 mask sample shows the highest filtration efficiency (99.9%) in the analysis. The simulation is consistent with the experimental results as the concentration of sodium chloride (NaCl) droplets is < 4% on average in the room. The ultraviolet-C (UVC) irradiation and dry heating samples are shown to retain the highest filtration efficiencies (> 97%) after 3 disinfection treatment cycles. All methods (boiling, steaming, ethanol treatment, and dry heating) effectively reduce the S. aureus load by 99.99%. The UVC irradiation shows exposure to 450 µW cm−2 for 10 minutes can effectively eliminate all S. aureus on the mask materials. Simulation shows the reduction in overall NaCl and carbon dioxide (CO2) levels is directly proportional to the filtration efficiency and the effectiveness of reused masks is also directly proportional to the filtration efficiency. The proxy indicator (CO2) for aerosol particles demonstrates that very fine respiratory droplets can penetrate the mask after reaching a steady state. The CO2 concentration increase shows that aerosol particles are accumulated under adequate ventilation and further pose the risk of infection. The NaCl droplets (2%) simulation shows that respiratory droplets have infiltrated the mask, but the mask demonstrates a higher ability to block the NaCl droplets and prevent their penetration. The findings suggest a need to revise the existing regulation of the control policy.